Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen MONSTER.INC Cianjur) - Andre Syaputra; Dekrita Komarasakti (Jurnal Ekonomi Manajemen Perbankan, 2020)
AbstractThis research was conducted to study and analyze the most dominant factors influencing purchasing decisions on Monster.Inc. The analytical method used is descriptive analysis method and multiple linear regression analysis. The data is processed statistically with SPSS version 24, namely the t test model, F test, and the coefficient of determination. The results of this study indicate that: (1) there is a positive and significant influence on the purchase decision of Monster.Inc, as evidenced by the value of T_count (4,783)> T_table (1,987) and the significance value (0,000) <0.05; (2) a positive and significant result is needed for the purchase decision on Monster.Inc, evidenced by the value of T_count (5.137)> T_table (1.987) and the significance value (0.000) <0.05; (3) related to positive and significant changes in product price and quality on purchasing decisions at Monster.Inc, as evidenced by the Fcount value of 36,580> Ftable 3,102 and a significance of F of 0,000. R Square value of 0.460 or 46% means that the purchase is based on variable price and product quality, while the remaining 54% is considered by other variables not related in this study.